The Diagnostic Dilemma: Should AI Be Used in Mental Health Diagnosis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming clinical practice, but few areas are as ethically and clinically comple...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning